Incentives for postmortem organ donation: ethical and cultural considerations - Ravitsky, Vardit (Journal of medical ethics, 2013)
Chronic shortage in organs for transplantation worldwide is leading many policy-makers to consider various incentives that may increase donation rates.1 These range from giving holders of donor cards some priority on the transplant waiting list or a discount on health insurance premiums, to giving families who consent to donation a medal of honour, reimbursement of funeral expenses, tax incentives or even financial compensation.2-4 Of the various proposed incentive mechanisms, the one that has consistently garnered the most criticism and objection in the literature is that of paying families who consent to donate the organs of a deceased loved one. Arguments against such a policy abound: it could exploit the poor, influence the family to prematurely withdraw care, encourage families to withhold medical information that would result in transplant-transmission of disease, and finally, it would commercialise the value of human life and result in the perception of human organs as commodities. Indeed, to date no Western country has adopted a policy of financial compensation to families for consenting to organ donation.2 Recently, a country suffering from severe shortage in organs has implemented a policy of financial incentives that uses cash payments. Wu and Fang5 describe a recent pilot programme in China that compensates families for postmortem donation, through an independent third party (the Red Cross Society of China) and based on consent or presumed consent (ie, no documented past objection) of the deceased. The particular context within which this programme is implemented validates and even exacerbates some ethical concerns that have been voiced in the Western medical and bioethics …